Institutions, Trade and Development: A Quantitative Analysis - Cosimo Beverelli; Alexander Keck; Mario Larch; Yoto V. Yotov (Center for Economic Studies and ifo Institute (CESifo), 2018)
We propose and apply methods to quantify the impact of national institutions on international trade and development. We are able to identify the direct impact of country-specific institutions on international trade within the structural gravity framework. Our approach naturally addresses the prominent issue of endogenous institutions. The empirical analysis offers robust evidence that stronger institutions promote trade. A counterfactual analysis reveals that the changes in institutional quality in the poor countries in our sample between 1996 and 2006 have had, via their impact on imports from rich countries, significant and heterogeneous real GDP effects, varying between -5 and 5 percent. Our methods are readily applicable to identifying the impact of a wide range of country-specific variables on international trade.
Keywords: F13; F14; F16; 330; institutional quality; international trade; development; structural gravity